Multikulturalisme Digital: Mengeksplorasi Integrasi Teknologi dalam Pengajaran Sekolah Dasar di Abad 21 - Sari, Atikah Atsfa (Indonesian Journal Publisher, 2024)
Technology and education, nowadays, are two things that cannot but be linked. Technology can bring the education system towards a higher quality model and education will also have a broader impact on technology. Based on these facts, this research was written with the aim of exploring the integration of technology in elementary school teaching in the 21st century. In writing this research, it was carried out using a descriptive method by collecting previous articles/journals to be used as a reference source in writing. The sources that have been collected are then subjected to in-depth analysis so that the expected conclusions can be found. The research results show that the integration of technology has a good impact on the world of education. Where technology plays a major role in the distribution of knowledge. Technology that has unlimited and limitless properties will have a positive impact on the world of education so that the boundaries that previously existed will be eroded due to the convenience provided.